Occurrence of polycyclic aromatic hydrocarbons (PAHs) in coral reef fish from the South China Sea. (February 2019) - Li, Yali; Wang, Chenglong; Zou, Xinqing; Feng, Ziyue; Yao, Yulong; Wang, Teng; Zhang, Chuchu
Abstract: Little data are available on the bioaccumulation of polycyclic aromatic hydrocarbons (PAHs) in coral reef fish from the South China Sea (SCS). In this study, we collected 21 coral reef fish species from the Xisha and Nansha Islands in the SCS to investigate the occurrence of 16 US-EPA PAHs. The total PAH concentrations (ΣPAH) in the collected fish ranged from 12.79 to 409.28 ng/g dry weight (dw, Xisha Islands) and from 32.71 to 139.09 ng/g dw (Nansha Islands), respectively. The ΣPAH concentration of Scarus niger collected from the Xisha Islands (237.13 ng/g dw) was about twofold higher than that of Scarus niger collected from the Nansha Islands (139.09 ng/g dw). The dominant compounds were found to be 2-ring and 3-ring PAHs. Based on qualitative and quantitative analyses, the main PAH sources were found to be coal and biomass combustion (50.43%), petroleum sources (25.86%), and vehicular emissions (16.10%). Highlights: The first report on PAH contamination in coral reef fish from the South China Sea PAH levels from the Xisha Islands were higher than those from the Nansha Islands Low molecular weight PAHs were dominant in coral reef fish PAHs mainly originated from biomass combustion, petroleum sources, and vehicular emissions